The Crystal Structure of Iron Doped Zinc Sulphide Prepared by the Chemical Bath Deposition Method (Sebha University Conference Proceedings, 2025)
Zins sulphide doped Iron thin films (Zn1-xFexS; x=0.0 &0.1)were prepared using the chemical bath deposition method(CBD). The films were annealed at 400o C for 1h.The crystal structural and morphological properties were characterized using the X-Ray diffractometer (XRD), the field emission scanning electron microscope (FE-SEM) and the atomic force microscope (AFM). The XRD results showed that the films have a cubic structure, The 2θ  diffraction peaks were shifted to the lift side due to the Fe ion interned in ZnS structure. The crystalline size of the films decreased from 3.4 to 1.1 nm  with increasing Fe concentration. The grains size of the films was also observed to be decreased to 1nm with increased Fe concentration. The RMS of films showed a different behavior were it increased up to 5.9 nm  with  increasing of Fe concentration